Case Report: A Candida Meningitis in an Immunocompetent Patient Detected Through the Next-Generation Sequencing - Cao, Xiao-guang; Yu, Chuang-wei; Zhou, Shu-sheng; Huang, Yu; Wang, Chun-yan (Frontiers in Medicine, 2021)
BACKGROUND Fungal infections of the central nervous system are not commonly seen clinically. Clinical diagnosis of Fungal infections often depends on pathogen culture and clinical features. This method is time-consuming and insensitive, which can lead to misdiagnosis. The authors introduce an adult patient with Fungal infections diagnosed by next-generation sequencing (NGS). CASE SUMMARY The patient was a 60-year-old Chinese male who had both hypermyotonia of lower extremities and fever. The auxiliary examinations such as MRI, CT and CSF analysis showed obvious abnormalities. Due to the difficulties in diagnosis, it was hard to determine the treatment plan. Next-generation sequencing(NGS) detected specific sequences of Candida albicans in three days. The patient was then treated with liposomal amphotericin B and Dufcon. About three weeks later, the symptoms of the patients improved significantly and he was discharged from the hospital. CONCLUSION Compared with the routine cultural method，NGS has made a huge advance in infection diagnosis and targeting antimicrobial therapy for central nervous system infection.